Genital warts and human papillomavirus vaccination. Issue 10 (October 2013) - Mehta, Milan M; Salem, Lara; Kemp, Timothy
Genital warts, or condylomata acuminata, are caused by the human papillomavirus (HPV). They are the most commonly diagnosed viral sexually transmitted infection in the UK. This article aims to describe the natural history of HPV and how to recognise and manage genital warts. A summary of the UK HPV vaccination programme is also included.